THE EVALUATION OF COMPLIANCE TO ANTIHYPERTENSIVE THERAPY IN PATIENTS AFTER STROKE AND POSTSTROKE DEPRESSION DURING ANTIDEPRESSANT THERAPY - B. B. Fishman; A. I. Khoroshevskaya; A. A. Abdulin; G. G. Semenova; P. V. Starikov; O. V. Pavlova (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study the effect of the antidepressant paroxetine on the compliance to antihypertensive therapy in patients with arterial hypertension (HT) and post-stroke depression.Material and methods. Patients (n=24) aged 55-73 with controlled HT (blood pressure, BP<140/90 mm Hg) and with subclinical poststroke depression after rehabilitation course were included into the study. Patients were split into two groups. Patients of group 1 (n=12) received adequate antihypertensive therapy and selective serotonin reuptake inhibitor paroxetine. Patients of group 2 (n=12) received antihypertensive therapy only. The study duration was 16 weeks. Patient compliance to antihypertensive therapy, BP and severity of depressive disorders, motor and intellectual functions was evaluated initially and after 16 weeks.Results. BP>140/80 mmHg after 16 weeks was found in 10 (41.6%) patients. Clinical post-stroke depression was found in 7 (30.4%) patients, 5 (41.6%) of them were from group 2 (OR=0.35, 95% CI 0.12-0.78). High treatment compliance was in 15 (65.2%) patients, and 9 (81.8%) of them were from group 1. Nine (39.1%) patients did not receive an adequate antihypertensive therapy, 5 (41.6%) of them were from group 2 and could not explain their refusal from medication. General index of intellectual function was higher in patients of group 1 (p=0.034) than this in group 2; index of motor function did not change significantly (p>0.05).Conclusion. Reduction of compliance to antihypertensive therapy and rehabilitation in hypertensive patients after stroke is associated with unmotivated refusal from treatment because of clinical post-stroke depression.